X-ray production by 500 MeV electron beam in a periodically structured monocrystalline target of GaAs; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 173, № 1-2 - Kaplin V. V. Valeriy Viktorovich; Kuznetsov S. I. Sergey Ivanovich; Timchenko N. A.; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich (2001, 2001)
Title screen